Organic carbon distribution between structural and process pools in the gray forest soil of different land use - T. N. Lebedeva; D. A. Sokolov; M. V. Semenov; N. B. Zinyakova; S. N. Udal’tsov; V. M. Semenov (Бюллетень Почвенного института им. В.В. Докучаева, 2024)
The summarized data on the content of organic carbon (Corg) in the subtypes of gray forest soils occurring on the territory of Russia was presented. It was shown that the humus horizons of virgin light-gray, typical-gray, and dark-gray forest soils contain, on average, 2.16 ± 0.67, 2.42 ± 0.61, and 3.58 ± 0.95% Сorg, respectively, while the plowing layers of arable soils contain 1.36 ± 0.40, 1.71 ± 0.40, and 2.84 ± 0.86%, respectively. Structural (particulate organic matter 0.05–2 mm in size, CPOM, and mineral-associated organic matter <0.05 mm in size, CMAOM) and process (potentially mineralizable organic matter, C0, and microbial biomass, Cmic) pools were isolated in the organic matter of samples from different horizons of gray forest soils (Luvic Retic Greyzemic Phaeozems (Loamic)) under small-leaved forest and barley crop. The CPOM/CMAOM ratio in the upper soil horizons under forest and arable land was 0.60 and 0.26, respectively, and this ratio decreased with depth to 0.05 under both land uses. The sizes of the CMAOM, CPOM, C0, and Cmic pools correlated with each other and depended on the depth of the soil horizon, while the effect of land use on the pool ratios was found only for the surface horizons. The contribution of CPOM and CMAOM to the potentially mineralizable pool of organic matter in gray forest soil was 20–41 and 71–87%, respectively. According to the obtained data, the size of the C0 pool was almost equal to the annual amount of the heterotrophic CO2 emission from the soil. It was emphasized that determining of the sizes and ratios of structural and process soil organic matter pools should be important in the programs of carbon monitoring and recarbonization of agroecosystems.